2016
DOI: 10.1073/pnas.1523465113
|View full text |Cite
|
Sign up to set email alerts
|

Age-aggregation bias in mortality trends

Abstract: In PNAS, Case and Deaton (1) show a figure illustrating the "marked increase in the all-cause mortality of middle-aged white non-Hispanic men and women in the United States between 1999 and 2013." The authors state that their numbers "are not age-adjusted within the 10-y 45-54 age group" (1).We suspected an aggregation bias and examined whether the increase in aggregate mortality rates could be due to the changing composition of this age group. Adjusting for age confirmed this suspicion. Contrary to Case and D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 1 publication
0
37
0
Order By: Relevance
“…Case and Deaton 34 and Gelman and Auerbach 35 also showed that age-adjusted mortality rates for white men aged 45 to 54 years were constant or increasing during the 2000s. Our finding of increasing life expectancy across most income groups differs from this result because our estimates incorporate declines in mortality rates at older ages, pool all races, and exclude individuals with 0 earnings at the age of 40 years.…”
Section: Discussionmentioning
confidence: 96%
“…Case and Deaton 34 and Gelman and Auerbach 35 also showed that age-adjusted mortality rates for white men aged 45 to 54 years were constant or increasing during the 2000s. Our finding of increasing life expectancy across most income groups differs from this result because our estimates incorporate declines in mortality rates at older ages, pool all races, and exclude individuals with 0 earnings at the age of 40 years.…”
Section: Discussionmentioning
confidence: 96%
“…Since publication of the original Case and Deaton report, efforts have been made to specify how the patterns observed vary across race, age, and gender. 18,19 When one looks at the big picture—with data spanning decades—we see that suicide rates are barely higher than they were in 1980 (Figure 1). We also see that deaths from alcoholic cirrhosis have increased only mildly since then.…”
Section: The True Deaths Of Despairmentioning
confidence: 98%
“…To avoid suppressed death counts due to low numbers we pooled 7 year estimates: the first period includes data from 1999 to 2005 while the second period spans from 2009 to 2015 To address potential age-aggregation bias (Gelman and Auerbach, 2016) we averaged mortality rates in people aged 45-49 and 50-54 to create an ageadjusted mortality rate for people aged 45-54. To estimate increases in mortality by county, we subtracted the mortality rate in the first period (1999)(2000)(2001)(2002)(2003)(2004)(2005) from the rate in the second period (2009)(2010)(2011)(2012)(2013)(2014)(2015).…”
Section: Health Datamentioning
confidence: 99%